The Influence of Financial Literacy, Job Training and Interest in E-Commerce on MSME Performance with Technology Availability as an Intervening Variable - Susanti; Imam Abu Hanifah; Ewing Yusiva Ibrani (Indonesian Journal of Economic & Management Sciences, 2024)
This research aims to determine the influence of Financial Literacy, Job Training, Interest in E-Commerce on the Performance of MSMEs in Banten Province with the availability of technology as an intervening variable. The population in this study were MSMEs in Banten Province, the sample was determined using a purposive sampling technique. The results show that Financial Literacy has a positive and significant effect on MSME Performance. Job training has a negative and significant effect on MSME performance. E-Commerce interest has a positive and insignificant effect on MSME performance. Furthermore, Financial Literacy has a positive and significant effect on Technology Availability. Job Training has a negative and insignificant effect on Technology Availability. E-Commerce Interest has a positive and significant effect on Technology Availability. Availability of Technology and has a positive and significant effect on MSME Performance. Financial Literacy has a positive and significant influence on MSME Performance with Technology Availability as an intervening variable. Job Training has a negative and insignificant effect on MSME Performance with Technology Availability as an intervening variable. E-Commerce Interest has a positive and significant influence on MSME Performance with Technology Availability as an intervening variable